Muscle architecture in patients with primary Sjögren syndrome - Duygu Tecer,; Dilek Eker Büyüksireci,; Zafer Günendi,; Jale Meray,; Feride Göğüs, (Archives of Rheumatology, 2023)
Objectives: This study aims to investigate skeletal muscle architecture and strength in patients with primary Sjögren syndrome (pSS). Patients and methods: Between July 01, 2017 and November 30, 2017, 19 pSS patients (19 females; mean age: 54.1±6.6 years; range, 42 to 62 years) and 19 age-, body mass index-, and sex-matched healthy controls (19 females; mean age: 53.2±6.7 years; range 42 to 61 years) were included. Sjögren symptoms were assessed with the European Alliance of Associations for Rheumatology (EULAR) Sjögren’s Syndrome Patient Reported Index (ESSPRI). Muscle thickness, pennation angle, and fascicle length were measured at quadriceps femoralis, gastrocnemius and soleus muscles. Isokinetic muscle strength tests were performed at 60 and 180°/sec for knee and at 30 and 120°/sec for ankle. Anxiety and depression evaluated with the Hospital Anxiety and Depression Scale (HADS), fatigue with Multidimensional Assessment of Fatigue scale (MAF), and functionality with Health Assessment Questionnaire (HAQ). Results: In the pSS group, the mean ESSPRI was 7.70±1.17. The mean scores of depression (10.05±3.09 vs. 4.47±2.29; p<0.0001), anxiety (8.26±4.28 vs. 3.79±2.42; p<0.0001), functionality (0.94±0.78 vs. 0.22±0.26; p<0.0001), and fatigue (37.69±5.47 vs. 17.69±5.26; p<0.0001) were significantly higher in patients with pSS. Only, the pennation angle of vastus medialis in dominant leg was significantly greater in healthy controls (p=0.049). Peak torques/body weight of knee and ankle muscles were found to be similar. Conclusion: Excluding a minor decrease of the pennation angle at vastus medialis, muscle structure of lower extremity of pSS patients were similar to healthy controls. In addition, isokinetic muscle strength did not significantly differ in patients with pSS compared to healthy controls. In patients with pSS, disease activity and fatigue level were negatively correlated with isokinetic muscle strength measurements.